Topological grounds for the fast kinematic dynamo origin in a knotted thermonuclear reactor - Maksyuta, M.V.; Golovach, G.P.; Martysh, Ye.V. (Вопросы атомной науки и техники, 2013)
The paper deals with the topological grounds for the possibility of effective fast kinematic dynamo origin in socalled knotted thermonuclear reactors. On the basis of the utilization of the topologic spirality invariant the additional arguments in favour of plasma strings stability raise in such reactors are given. It is supposed that in the reactors with cavities like linking torical knots plasma confinement characteristics may be essentially improved that would allow carrying out thermonuclear synthesis.